Elaboración de un plan estratégico para la cooperativa de transportes pesados Cital de la ciudad de Loja, provincia de Loja - Espinosa Iñiguez, Mauricio Antonio (2015)
Economic and political instability that suffered for many years the Ecuador caused the bankruptcy of many companies and the departure of others in the country, affecting the freight transportation sector due to rising of their work and the high operating costs did not allow improve their services. Although the political and economic problems remain in the country, the situation has improved in recent years regarding the production activity of industries, leading to increased exports and imports as well as business development in the country, with Heavy transport an important factor in the national economy to move goods and supplies in and out of the country. Since the demand for freight transportation has increased, carriers have found it necessary to improve their services, which have been linked through the formation of cooperatives and freight companies allowing them to achieve more favorable conditions for the development of their activities. However, as the Ecuador market attractive freight transport, competition from local carriers and cargo transnational companies that have managed to become citizens and legally operate in the country is present. Cooperative Heavy Haulage Cital in the beginning was a leader in the province, and that having fifteen partners have sufficient work for its members, at present by the lack of organization has been losing competitiveness and positioning market, which is why the partners have been forced to rely on other carriers. An alternative solution is proposed for Cital, is the design of a marketing plan, which will enable the completion of the analysis of their situation and based on the results contribute to a business address, so that the approach would constitute a support viable administrative management of the company. The development of this marketing plan will allow the Cooperative Freight Heavy Cital raise and evaluate strategies to propose to improve the current situation of the company. Among the results of the investigation it was determined EFE matrix which has a weighting of 2.41 which implies that the company has an internal potential which can confront the threats and seize the opportunities offered by the market. While the IFE Matrix has a weighting of 2.44 which suggests that there problems strengths and weaknesses. The project budget is as follows: PROJECT COST ADVERTISING FOR HEAVY TRANSPORT COOPERATIVE CITAL $ 2.657,20 TRAINING FOR EMPLOYEES OF HEAVY TRANSPORT COOPERATIVE CITAL $ 1.800,00 IMPROVE THE POSITIONING OF HEAVY TRANSPORT COOPERATIVE CITAL CITAL $ 1.600,00 ACHIEVE PROPER TECHNOLOGICAL DEVELOPMENT AND DYNAMIC $ 700,00 TOTAL $ 6.757,20